2015
DOI: 10.1021/acs.nanolett.5b01919
|View full text |Cite
|
Sign up to set email alerts
|

A Graphene-like Oxygenated Carbon Nitride Material for Improved Cycle-Life Lithium/Sulfur Batteries

Abstract: Novel sulfur (S) anchoring materials and the corresponding mechanisms for suppressing capacity fading are urgently needed to advance the performance of Li/S batteries. Here, we designed and synthesized a graphene-like oxygenated carbon nitride (OCN) host material that contains tens of micrometer scaled two-dimensional (2D) rippled sheets, micromesopores, and oxygen heteroatoms. N content can reach as high as 20.49 wt %. A sustainable approach of one-step self-supporting solid-state pyrolysis (OSSP) was develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
213
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(217 citation statements)
references
References 42 publications
3
213
1
Order By: Relevance
“…The ACNF@MnO 2 electrode without CNT suffers from poor rate capability due to slow electron and ion transport ( Figure S8). Figure S9) [42,43]. The discharge plateaus correspond to the reduction of elemental sulfur to high-order polysulfides and then to Li 2 S/Li 2 S 2 , while the charge plateaus represent the reverse process ( Figure S10) [44].…”
Section: Resultsmentioning
confidence: 99%
“…The ACNF@MnO 2 electrode without CNT suffers from poor rate capability due to slow electron and ion transport ( Figure S8). Figure S9) [42,43]. The discharge plateaus correspond to the reduction of elemental sulfur to high-order polysulfides and then to Li 2 S/Li 2 S 2 , while the charge plateaus represent the reverse process ( Figure S10) [44].…”
Section: Resultsmentioning
confidence: 99%
“…The design of multi-architectural and multi-functional cathode materials has the potential to overcome these challenges and has been one of the most researched strategies in recent years. Currently, physical routes including capillary force absorption [14,[51][52][53][54][55][56][57], shell coating [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75], and chemical routes containing heteroatom-doped carbons [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] and metal-based additives [91][92][93][94][95][96][97][98][99]…”
Section: Fundamental Studies and Materials Selectionmentioning
confidence: 99%
“…[18] Furthermore, the cycled CÀCNN/S sample was collected by disassembling the cycled LiÀS battery cell and characterized by XPS. As shown in Figure 10 c, the N 1s XPS of the CÀCNN/S before cycling was resolved to three main peaks at 398.7 eV for pyridinic N, 399.7 eV for pyrrolic N, and 401.1 eV for graphitic N. [48,49] After cycling, the peaks at 398.7 eV and 399.7 eV shifted to 399.3 eV and 399.9 eV, while the peak at 401.1 eV was almost invariable (Figure 10 e), further indicating the existence of chemical interaction between LiPS and pyridinic, pyrrolic nitrogen. The post-mortem SEM image in Figure S9 revealed that some lithium polysulfides particles were adsorbed and deposited on the surface of CÀCNN after long cycling, which further confirmed the strong chemical interactions between CÀCNN and LiPS.…”
mentioning
confidence: 94%